Decentralization in Colombia, responsibilities and fiscal autonomy of the municipality of Cajicá (2013)
In the present paper makes a historical review of the decentralization process in Colombia with competitive analysis, institutional capacity, interaction making levels of government emphasis on Cajicá work of the years 2011-2013, therefore it is presents the evolution of Cajicá budget, analyzing the source of funding, investment budget lines since 2011-2013 that reflect the municipality's own ability to carry out its functions meet the needs of its inhabitants.